On generalizations of Soft Fuzzy Gδ Semi-Closed Sets - Visalakshi, V.; Vidhya, D.; Yogalakshmi, T. (International Journal of Engineering and Technology, 2018)
In this paper, soft fuzzy Gδ semi closed set is introduced. Using soft fuzzy Gδ semi closed set, generalized soft fuzzy Gδ semi-continuous function, generalized soft fuzzy Gδ   semi-connected space, generalized  soft fuzzy Fσ semi-compact space are introduced and studied. In this connection, properties and characterizations are established. Also soft fuzzy T-Fσ space is introduced and studied. Examples and counter examples are provided wherever necessary.